Frequency Analysis of Complex Sentence Structures in English Written Texts: A Corpus-Based Study Using Brown and LOB Corpora - Ass.Lect Rafah Mazban Badan (Journal of College of Education, 2026)
Abstract: Complex sentences constitute a universal feature of human language, characterised by their intricate syntactic structures and diverse types of embedded clauses, thereby establishing them as a focal point in linguistic research. This study employs the Brown and LOB written English corpora to conduct a quantitative analysis of complex sentence frequency across four dimensions: overall usage, genre, language variety (American versus British English), and the types and numbers of subordinate clauses. Key findings reveal that genre significantly influences complex sentence frequency, with the highest usage observed in religious texts, literature, biographies, and essays—attributed to their formal or serious tone—whilst fiction exhibits the lowest frequency. In contrast, language variety demonstrates no statistically significant impact. Notably, both the type and number of subordinate clauses within complex sentences significantly affect their frequency. Contrary to prior studies, relative clauses (in both American and British English) do not rank as the least frequent, thereby challenging existing linguistic assumptions.